Glaucoma as a Neurodegenerative Disease. (September 2015) - Danesh-Meyer, Helen V.; Levin, Leonard A.
Abstract : Background: The primary pathophysiological feature of glaucoma is a progressive optic neuropathy with characteristic morphological changes of the optic disc and risk factors of age and intraocular pressure. Recently, involvement of other areas of the central nervous system (CNS) beyond the optic nerve has been demonstrated. This article addresses the proposition that glaucoma shares mechanistic and pathophysiologic features with neurodegenerations in the CNS. Methods: The literature on CNS alterations in patients with glaucoma is reviewed with particular focus on neuroimaging and pathological studies. A theoretical framework for assessing whether glaucoma is truly a neurodegenerative disease is developed based on the comparison with neurodegenerative and nonneurodegenerative diseases. Results: Although there is convincing evidence of abnormalities in CNS regions distal to the optic nerve in glaucoma, these are similar to those seen in other disorders of the proximal visual pathways, such as other optic neuropathies or retinal diseases. Similarly, features of glaucoma that are similar to neurodegenerations are also seen in nonneurodegenerative diseases. Conclusions: Glaucoma is less likely a primary neurodegeneration affecting the CNS and more likely a primary optic neuropathy with secondary effects in the CNS.